Reconfigurable phased microstrip antenna array with defected ground structure and defected microstrip structure for beam steering application - Subhi Ahmad, Khalid (2018)
Beam steering is defined as the ability to electronically steer the beam maximum of an antenna electric field pattern to some predefined point in space. The performance of a phased antenna array for beam steering without moving the antennas is important to military and civil applications. A steerable antenna with tunable phase shifter continues to be a popular choice to provide such systems. However, this additional device makes the structure more complicated, bulky and it represent a great part of the production cost of a phased array antenna. Therefore, it creates new challenges to find an alternative approach. This work proposed two alternative approaches to steer the main beam. The first is based on a defected ground structure (DGS), while the second is a defected microstrip structure (DMS), which due to their slow wave effect and band-stop property, are able to disturb surface current distribution, then change the element phase and hence steer the main beam. This work started with investigating and applying new method for beam steering based on using DGS and DMS, where this reflects the first objective. As a second objective, this work proposed new approach for beam steering, where DGS is integrated between two patches for the bandwidth within X-band. The simulated results revealed the achievement of the target to steer the main beam to 50° along H-plane. For the third objective, a spiral antenna array (SAA) has been proposed, and it was observed that the best choice for selecting feed network for feeding circular antenna array is a common sequential feed network (SFN), which has a circular shape with four ports to feed four elements. In order to increase the number of ports and hence design suitable feed network for feeding SAA, this study proposed new spiral sequential feed network (SSFN). As a dual structure of DGS, and compared with DGS, DMS is of great advantage in design due to its reduced size and the feature of electromagnetic interference noise immunity. Furthermore, DMS has higher effective inductance compared to DGS. Therefore, this work proposed new reconfigurable SAA with DMS fed by SSFN within C-band. The simulated results showed the achievement of the target to steer the main beam to 61° and 84° along E-plane and H-plane, respectively. Furthermore, as the last objective, a new approach was proposed for extracting equivalent circuit model for DGS with dual patches, SSFN and SAA. Two prototypes of dual patches with and without DGS, SSFN and two prototypes of SAA with DMS were fabricated for scattering parameter and far-field radiation pattern measurements. The results showed close agreement with the predicted results, where array with DGS confirmed a beam steering of 36° along H-plane, while SAA with DMS displayed 45° beam steering along E-plane, respectively. Future works will focus on increasing the array gain and reducing the array beam width which will give a clear vision for beam steering of array.